Irradiation‐Wavelength Directing Circularly Polarized Luminescence in Self‐Organized Helical Superstructures Enabled by Hydrogen‐Bonded Chiral Fluorescent Molecular Switches. (21st October 2021) - He, Yanrong; Zhang, Shu; Bisoyi, Hari Krishna; Qiao, Jinghui; Chen, Hong; Gao, JingJing; Guo, Jinbao; Li, Quan
Abstract: Two light‐driven chiral fluorescent molecular switches, ( R, S, R )‐switch 1 and ( R, S, R )‐switch 2, are prepared by means of hydrogen‐bonded (H‐bonded) assembly of a photoresponsive ( S ) chiral fluorescent molecule, respectively with a cyano substitution at different positions as an H‐bond acceptor and an opposite ( R ) chiral molecule as an H‐bond donor. The resulting two switches exhibit tunable and reversible Z / E photoisomerization irradiated with 450 nm blue and 365 nm UV light. When doped into an achiral liquid crystal, both switches are found to be able to form a CPL tunable luminescent helical superstructure. In contrast to the tunable CPL characteristics of the system incorporating switch 2, exposure of the system incorporating switch 1 to 365 nm and 450 nm radiation can lead to controllable different photostationary CPL behavior, including switching‐off and polarization inversion. In addition, optical information coding is demonstrated using the system containing switch 1 . Abstract : Phototuning the turning‐off and the polarization inversion of circularly polarized luminescence signals is obtained in the corresponding photostationary state of the same helical cholesteric superstructure constructed from the light‐driven hydrogen bonded chiral fluorescent molecular switch, which derives from the different conversion ratio of Z / E photoisomerization of the switch upon different light irradiations.